ANALYSIS OF CONSERVATION LITERACY OF PROSPECTIVE BIOLOGY TEACHERS AND EFFORTS TO IMPROVE IT THROUGH INTEGRATED CAMPUS PROGRAMS - Aswin, Pani; Rahmayanti, Rita; Rahmadayanti, Annesha; Kasrina (Jurnal Pelita Pendidikan, 2025)
This study aims to describe the level of conservation literacy of prospective biology teachers. Data were obtained through a survey using a Likert-scale questionnaire with three main aspects (knowledge, attitudes, and skills). Respondents were seventh-semester students who completed the instrument online. The resulting data were then analyzed descriptively. The results showed that the knowledge aspect was classified as good, although participation in scientific forums was still low. The attitude aspect was categorized as very good, but discipline in energy conservation needs to be improved. The skills aspect was classified as good but needed strengthening through creative activities such as composting, ecobricks, and school conservation projects. The conservation action aspect was not optimal because the activities were still individual and simple, so support and training were needed to encourage collaborative involvement. The conclusion of this study confirms that the conservation literacy of prospective biology teachers is quite developed at the level of knowledge and attitudes, but is still limited in the implementation of concrete actions.